EVALUATION OF THE INFLUENCE OF THE AERODYNAMIC COEFFICIENTS OF THE FRONTAL RESISTANCE FORCE OF THE PROJECTILE ON ITS FLIGHT DISTANCE - Bondarenko, S. V.; Kosovtsov, Yu. M.; Hrabchak, Z. M. (Systems and Technologies, 2024)
An urgent and important issue in the creation and development of promising anti-artillery systems and ammunition for them is the introduction of automated control systems with the wide use of ballistic computers, which include new approaches to ballistic and meteorological data preparation for firing, the mathematical basis of which are ballistic integrating algorithms for calculating installations for firing based on solving the inverse problem of external ballistics. An important component of the aerodynamic force vector acting on the projectile is the drag force, which has a direction opposite to the direction of the projectile’s velocity and significantly affects the dynamics of its flight. The practical application of the theoretical provisions of the research of frontal resistance is their use for calculating projectiles flight trajectories and compiling the firing tables of artillery systems, therefore, the accuracy of the tabular range calculation is taken as a measure of the accuracy of its determination. The analysis of requirements for the accuracy of calculation of the tabular range of artillery systems shows that the value of the median error at short firing ranges has a value of the order 0.50% of the flight range, at long ranges – (0.25 ÷0.30)%. The experimental study of the drag force is reduced to the study of its aerodynamic coefficients at different values of Mach numbers. In addition, it is important to evaluate the influence of both the linear and non-linear components of the aerodynamic drag force coefficient on the range of the projectile. To evaluate the influence of aerodynamic coefficients on the flight range of the projectile, the difference method was used, which consists in solving the system of differential equations of spatial motion of a projectile so that, by changing the value of each of the component aerodynamic coefficients, a change in the value of the flight range is obtained. Numerical modeling of the dependence of the flight range error of 155-mm HE projectiles – Assegai M2000 and ERFB/BB on a change in the value of their aerodynamic coefficients by 1%. It is shown that the largest error in the flight range of the projectile is introduced by the linear coefficient of the force of frontal resistance when firing at the maximum charge – 0.9% of the firing range, respectively, the smallest, at the minimum charge – 0.13%. In addition, the simulation results showed that the influence of the quadratic coefficient of the frontal drag force has 1-2 orders of magnitude smaller values compared to the linear one.